Plasminogen activator inhibitor type-1 (PAI-1) in tissue extracts of breast cancer - Pietrusińska, Elżbieta; Ziółkowska, Ewa; Kotschy, Maria (Contemporary Oncology/Współczesna Onkologia, 2004)
The growth and invasion of breast cancer are connected with the activation of plasminogen into plasmin degrading, directly or indirectly, through the metalloproteinases many components of extracellular matrix. Plasminogen activator inhibitor type-1 (PAI-1) may influence processes connected with tumor growth and progression through the regulation of plasmin generation. The aim of the work was to evaluate the concentration of PAI-1 in tissue extracts of breast cancer and compare it to normal breast tissues. The changes of PAI-1 concentration in cancer tissues depending on selected prognostic factors in breast cancer were also analyzed. The study involved 30 women with breast cancer aged between 39 and 81 (on average 58) treated in the Oncological Centre in Bydgoszcz. The fragments of tissues were taken from malignant tumors extracted during surgery together with the surrounding tissue or the whole breast. The basis of comparison was extracts from breast cancer tissues and macroscopically normal breast tissues located about 2 cm from the tumor. The concentration of PAI-1 in tissue extracts was determined using the enzyme immuno-assay kit (ELISA). A significantly higher concentration of PAI-1 was noticed in tissue extracts of breast cancer compared to normal breast tissues. The concentration of PAI-1 in cancer tissues was significantly much higher in tumors with worse prognosis, which in a group with advanced tumors is T2 and without estrogen receptors. Our study confirmed that PAI-1 takes part in the pathogenesis of breast cancer.